SHAŃARAQTÍŃ SOCIYAL-PEDAGOGIKALÍQ TIYKARLARÍ - Abdimuratova, N.P. (SCIENCE and SOCIETY, 2024)
The article deals with the mechanisms of preparing the younger generation for family life from a scientific and pedagogical point of view.